Towards the two-dimensional imaging of spontaneous ultra-weak photon emission from microbial, plant and animal cells - Prasad, Ankush; Pospíšil, Pavel (Scientific reports, 2013)
Two-dimensional imaging of spontaneous ultra-weak photon emission was measured in the yeast cells, Arabidopsis plant and the human hand using highly sensitive charge coupled device (CCD) camera. For the first time, the detail analysis of measuring parameters such as accumulation time and binning is provided with the aim to achieve two-dimensional images of spontaneous ultra-weak photon emission of good quality. We present data showing that using a hardware binning with binning factor 4 × 4, the accumulation time decreases in the following order: yeast cells (30 min) > the human hand (20 min) > Arabidopsis plant (10 min). Analysis of measuring parameters provides a detailed description of standard condition to be used for two-dimensional spontaneous ultra-weak photon imaging in microbes, plants and animals. Thus, CCD imaging can be employed as a unique tool to examine the oxidative state of the living organism with the application in microbiological, plant and medical research.
Keywords: časové faktory; Saccharomyces cerevisiae; Oxidation-Reduction; oxidace-redukce; Arabidopsis; ruka; Animals; Humans; Time Factors; lidé; fotony; zvířata; Photons; Hand